2021
DOI: 10.1111/anec.12900
|View full text |Cite
|
Sign up to set email alerts
|

Predictive impacts of chronic kidney disease and cardiac sympathetic nervous activity on lethal arrhythmic events in chronic heart failure

Abstract: Background The clinical implications of chronic kidney disease (CKD) and cardiac sympathetic nervous activity (CSNA) regarding lethal arrhythmic events have not yet been fully elucidated in patients with chronic heart failure (CHF). We hypothesized that the combination of CKD and abnormal CSNA, assessed by 123 I‐metaiodobenzylguanidine ( 123 I‐MIBG) scintigraphy, may provide useful prognostic information for lethal arrhythmic events. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…From the results of this study including the additional analysis, it is speculated that the patients with relatively preserved renal function, or not contraindicated to use diuretics (e.g. patients with hypertension and preserved renal function, often complicated with LVH) can be potentially reversible causes of cardiac sympathetic dysfunction among TAVI candidates for severe AS (27)(28)(29). The close relation of renal function and cardiac sympathetic nerve activity has been widely known for HF with both preserved and reduced LV function, so called cardiorenal syndrome (30).…”
Section: Discussionmentioning
confidence: 99%
“…From the results of this study including the additional analysis, it is speculated that the patients with relatively preserved renal function, or not contraindicated to use diuretics (e.g. patients with hypertension and preserved renal function, often complicated with LVH) can be potentially reversible causes of cardiac sympathetic dysfunction among TAVI candidates for severe AS (27)(28)(29). The close relation of renal function and cardiac sympathetic nerve activity has been widely known for HF with both preserved and reduced LV function, so called cardiorenal syndrome (30).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic activation of the SNS is prevalent in patients with T2D, ischemic heart disease, HF, hypertension, and CKD and results in fluid retention, endothelial dysfunction, and increased arterial stiffness [110]; chronic SNS activation is associated with poor prognosis [111][112][113][114][115]. The SNS is regulated, in part, by the kidneys, as renal stress results in increased signaling to the brain, stimulating the sympathetic center and enhancing sympathetic outflow [110].…”
Section: Reduction In Sns Activationmentioning
confidence: 99%
“…More recently, Marsico et al showed that, in a population of 263 patient with mild-to-severe HF, 123 I-MIBG uptake was significantly reduced in HF patients with severely impaired renal function compared to HF subjects with preserved renal function [39]. Furthermore, the combination of chronic kidney dysfunction and impaired cardiac sympathetic nervous activity, assessed by 123 I-MIBG scintigraphy, has been shown to have a high prognostic value in the prediction of lethal arrhythmic events in HF patients [40]. In conclusion, these results suggest that impaired cardiac sympathetic innervation might contribute to worsen prognosis in patients with HF and concomitant renal dysfunction.…”
Section: I-mibg Imaging In Hf Associated To Chronic Kidney Diseasementioning
confidence: 99%